2012
DOI: 10.3354/meps09379
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing thermal tolerance by eliminating the pejus range: a comparative study with three decapod crustaceans

Abstract: Marine invertebrates in the intertidal and subtidal zones are often exposed to highly variable environmental conditions, especially rapid changes in temperature. The ability to survive at different temperatures has previously been described using an extended version of Shelford's law of tolerance, with optimum, pejus (Latin: 'turning worse'), and pessimum ranges, and the respective thresholds, critical (T c ) and pejus (T p ) temperatures, that mark the transition from one range into the next. The width of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 39 publications
(29 reference statements)
3
42
0
Order By: Relevance
“…Although the two species were acclimated to different temperatures, as befitted the species, these data indicate that the lumpfish retained a lower oxygen supply capacity at CT max in normoxia when compared with red drum. It has been suggested that species occupying a wide thermal range (niche) have been evolutionarily selected for a more thermally resistant cardiorespiratory system (Ern et al, 2014;Jost et al, 2012). The differences in oxygen supply capacity at CT max , observed here for lumpfish and red drum, may therefore be related to the ecology of the two species.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although the two species were acclimated to different temperatures, as befitted the species, these data indicate that the lumpfish retained a lower oxygen supply capacity at CT max in normoxia when compared with red drum. It has been suggested that species occupying a wide thermal range (niche) have been evolutionarily selected for a more thermally resistant cardiorespiratory system (Ern et al, 2014;Jost et al, 2012). The differences in oxygen supply capacity at CT max , observed here for lumpfish and red drum, may therefore be related to the ecology of the two species.…”
Section: Discussionmentioning
confidence: 70%
“…It has also been suggested that oxygen-dependent upper thermal limits identified in the laboratory represent those in the field (Giomi et al, 2014;Pörtner and Knust, 2007). However, the link between oxygen supply capacity and upper thermal limits has recently been questioned, as other studies have reported that aerobic scope (AS, the difference between the maximum metabolic rate, MMR, and the standard metabolic rate, SMR) and cardiorespiratory performance are maintained in a number of fish and crustacean species experiencing ecologically relevant thermal extremes (Brijs et al, 2015;Clark et al, 2013;Ern et al, 2015Ern et al, , 2014Gräns et al, 2014;Healy and Schulte, 2012;Jost et al, 2012;Norin et al, 2014). It has, therefore, been suggested that some species possess a more thermally resistant cardiorespiratory system (Ern et al, 2014;Jost et al, 2012), and that insufficient tissue oxygen supply is not the primary determinant of upper thermal limits in all water-breathing ectotherms (Brijs et al, 2015;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In crustaceans, several studies over the past decade have reported such limitations in the oxygen supply capacity at high temperatures, revealed as a decline in cardiac and ventilatory performance as well as reductions in oxygen levels in the hemolymph with increasing temperature (Frederich and Pörtner, 2000;Frederich et al, 2009;Marshall et al, 2011;Jost et al, 2012). As further support for the OCLTT model, several marine invertebrates, including crustaceans, resort to anaerobic metabolism when approaching their upper thermal limit (Taylor et al, 1973;Taylor et al, 1977;Sommer et al, 1997;Frederich and Pörtner, 2000;Peck et al, 2002;Sokolova and Pörtner, 2003).…”
mentioning
confidence: 96%
“…Arguably, while organismal mortality, pessimum (least favourable conditions, usually the switch from aerobic to anaerobic respiration) and pejus (=getting worse; compromise of physiological performances) may be difficult to pinpoint in the study of plant stress response (c.f. [47] [48]), it is proposed in this study here that for photosynthetic parameters, F v /F m ratio approaches the pessimum (CT max : critical thermal maxima, see [49] [50]) if not the upper lethal limit of organismal survival while LT 50 values of photosynthetic O 2 evolution could represent the onset of photosynthetic compromises (pejus) due to the increasing heat stress.…”
Section: Critical Temperatures and Thermal Windowsmentioning
confidence: 99%